Opportunities and challenges for savanna burning emissions abatement in southern Africa. (15th June 2021) - Russell-Smith, Jeremy; Yates, Cameron; Vernooij, Roland; Eames, Tom; van der Werf, Guido; Ribeiro, Natasha; Edwards, Andrew; Beatty, Robin; Lekoko, Othusitse; Mafoko, Jomo; Monagle, Catherine; Johnston, Sam
Abstract: Savanna fires occurring in sub-Saharan Africa account for over 60% of global fire extent, of which more than half occurs in the Southern Hemisphere contributing 29% of global fire emissions. Building on experience in reducing savanna fire emissions in fire-prone north Australian savannas through implementation of an internationally accredited 'savanna burning' emissions abatement methodology, we explore opportunities and challenges associated with the application of a similar approach to incentivise emissions reduction in fire-prone southern African savannas. We first show that for a focal region covering seven contiguous countries, at least 80% of annual savanna large fire (>250 ha) extent and emissions occur under relatively severe late dry season (LDS) fire-weather conditions, predominantly in sparsely inhabited areas. We then assess the feasibility of adapting the Australian emissions abatement methodology through exploratory field studies at the Tsodilo Hills World Heritage site in north-west Botswana, and the Niassa Special Reserve in northern Mozambique. Our assessment demonstrates that application of a savanna burning emissions abatement method focused on the undertaking of strategically located early dry season (EDS) burning to reduce LDS wildfire extent and resultant emissions meets key technical criteria, including: LDS fine fuels tend to be markedly greater than EDS fuels given seasonal leaf litter inputs; LDS fires tend to be significantly more severe and combust more fuels; methane and nitrous oxide emission factors are essentially equivalent in EDS and LDS periods under cured fuel conditions. In discussion we consider associated key implementation challenges and caveats that need to be addressed for progressing development of savanna burning methods that incentivise sustainable fire management, reduce emissions, and support community livelihoods in wildfire-dominated southern African savannas. Highlights: Savanna wildfires in southern Africa contribute globally significant greenhouse gas emissions. We assess the technical feasibility of applying a savanna burning emissions reduction method. Based on field assessments in Botswana and Mozambique we find that such a method is applicable. Despite this, considerable implementation challenges are involved.